Cost Of Capital, Corporate Tax Plannings, And Corporate Social Responsibility Disclosure - Adhitya Jati Purwaka; Amrie Firmansyah; Resi Ariyasa Qadri; Agung Dinarjito; Zef Arfiansyah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study aims to determine the effect of tax management activities on the cost of capital and the role of social responsibility disclosure in moderating its impact. This study employs secondary data from financial statement data, stock price information, and 10-year government bond yields. The data was obtained from the websites www.idx.co.id, www.idnfinancials.com, www.finance.yahoo.com, and www.bloomberg.com. Using purposive sampling, the research sample is from manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020, obtaining 325 observations. Data were analyzed employing multiple linear regression for panel data. This study indicates that tax avoidance and tax aggressiveness are not associated with the cost of capital, while tax risk is negatively related to the cost of capital. Corporate social responsibility disclosure does not succeed in moderating the effect of tax avoidance and tax aggressiveness. Still, it succeeds in moderating the association between tax risk and cost of capital.